2005
DOI: 10.1074/jbc.m505087200
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Domain Nicotinic Acetylcholine Receptors Formed by α4 and β2 Subunits

Abstract: Models of the extracellular ligand-binding domain of nicotinic acetylcholine receptors (nAChRs), which are pentameric integral membrane proteins, are attractive for structural studies because they potentially are water-soluble and better candidates for x-ray crystallography and because their smaller size is more amenable for NMR spectroscopy. The complete N-terminal extracellular domain is a promising foundation for such models, based on previous studies of ␣7 and muscle-type subunits. Specific design requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(22 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…ligand binding) complexes, as shown previously by coexpression of intact ␣4 and ␤2 subunits (41) or ECDs carrying the transmembrane M1 domain (23). Gel filtration chromatography demonstrated that the coexpressed polypeptides existed mostly as microaggregated complexes (Fig.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…ligand binding) complexes, as shown previously by coexpression of intact ␣4 and ␤2 subunits (41) or ECDs carrying the transmembrane M1 domain (23). Gel filtration chromatography demonstrated that the coexpressed polypeptides existed mostly as microaggregated complexes (Fig.…”
Section: Discussionmentioning
confidence: 70%
“…Coexpression of the Mutated ECDs-We then attempted to coexpress the two mutated ECDs in an effort to obtain ligandbinding pentameric ECD complexes as shown by others using coexpression of intact ␣4 and ␤2 subunits (23,34). The two mECDs were expressed with different tags (␣4-mECD-FLAG and ␤2-mECD-His 6 ) to detect the coexistence of these molecules.…”
Section: Resultsmentioning
confidence: 99%
“…Using mutagenesis and affinity labeling, non-neighboring residues in the primary sequence of the protein were identified as important in ligand binding (4 -8). Several studies have shown expression of ␣7 nAChR extracellular domains (9 -11) or variants (12)(13)(14), yet none have resulted in crystal structures. Studies involving the Lymnaea stagnalis (Ls) and Aplysia californica (Ac) acetylcholine-binding proteins (AChBP) have yielded many structural analyses of the binding site for these mollusk homologues (15)(16)(17)(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…The feasibility of extracellular domain nAChRs was supported by studies with muscle-type subunits (163)(164)(165)(166)(167), α7 subunits (168)(169)(170)(171), and α4 and β2 subunits (172). Extracellular domain muscle-type subunits without any transmembrane domains formed pentamers detected by electron microscopy (165).…”
Section: Extracellular Domain Nachrsmentioning
confidence: 83%
“…Extracellular domain muscle-type subunits without any transmembrane domains formed pentamers detected by electron microscopy (165). Extracellular domain α7 and α4β2 nAChRs likely were pentamers and showed affinities for small and large ligands equal to the ligand affinities of the respective full length nAChRs (169,172). Retaining M1 on the extracellular domain, however, was required for efficient expression of extracellular domain α7 and α4β2 nAChRs.…”
Section: Extracellular Domain Nachrsmentioning
confidence: 99%